The Status-Achievement Process: Insights from Genetics - Nielsen, François (Frontiers in Sociology, 2016)
The mainstream status achievement model of sociology and economics views individual careers as sequences of causally linked status-related traits and outcomes such as ability, educational attainment, and occupational status. The variance decomposition models of quantitative genetics interpret variation in these traits and status outcomes as produced by latent factors summarizing genetic, shared environmental and nonshared environmental sources of influence. This article proposes that the two approaches can be combined and together provide valuable insights into core issues of social stratification research. The argument is illustrated with respect to three issue areas: (1) Nature of family environmental influences in educational attainment; (2) Sources of associations among successive status-related outcomes; (3) Implications of the combined status achievement / quantitative genetic model for the relative strengths of opportunities for mobility versus social forces of reproduction facing individuals in different social positions and in different societies.